Implementation of Curriculum Content Through Learning Planning - Tukiran Tukiran; Muhamad Rudi Wijaya (Universitas Pahlawan Tuanku Tambusai, 2022)
The role of education in terms of any aspect is also urgent. Learning planning which includes formulating what goals will be achieved by a learning activity, what methods are used for these purposes, what materials will be delivered, how to deliver them, and what tools or media are needed. While the curriculum content includes facts, data observation, perception, sensing, design, problem solving that comes from the human mind, from experience and the results of thought constructs that are organized, organized in the form of ideas, concepts, generalizations, principles, plans and solutions. problem. It is the task of the educator/teacher in this case, it is the teacher and/or lecturer to identify and carry out well the implementation of curriculum content development in the learning planning process